Effects of Machinery Compaction of Bernam Series Soil (Typic Endoaquepts) on Soil Properties and Oil Palm Performance - Yahya, Zuraidah (2010)
Mechanization was introduced to the oil palm plantations to overcome labor shortage and to improve production efficiency. The impact of soil compaction from the mechanization contributes to gradual alteration of soil physical properties. The information on severity and extent of soil degradation due to mechanization are still lacking. Hence, this study was carried out to determine the extent of soil degradation resulting from mechanization activities and its subsequent influence on oil palm performance. The study was carried out at Melentang Estate in Bagan Datuk, Perak, Malaysia. The site was a flat coastal terrain of clayey Bernam Series soil (Typic Endoaquepts). It was planted in 1996 with GH300 DxP materials at planting density of 148 palms per hectare and the trial was started in 2002. The treatments were combination of three trailer weights (0, 2 and 4 tonnes) and three transportation frequencies (1, 2 and 3 rounds monthly).Soil physical analyses and vegetative measurements were done twice a year. Yield was recorded every 10 to 12 days and root samplings were taken at the end of the trial. After six years of compaction treatments, the soil bulk density and total porosity were significantly increased and reduced by 30% and 15% respectively. Compaction was further indicated by a significant reduction of macropores by 10% and increment of mesopores and micropores by 10% and 3% respectively. This resulted in increased available water of the compacted soil by 19%. However, the soil hydraulic conductivity and infiltration rate were significantly reduced by 51% and 31% respectively. Most of the changes in the soil physical properties were found only within the first 0 to 10 cm depth of the harvesting path. Although soil compaction was expected to reduce the oil palm yield, the results show otherwise. The fresh fruit bunch (FFB) yield, bunch number and bunch weight increased by 11%, 14% and 2% respectively in the compacted plots as compared to control. However, the oil palm standing biomass in control plots was significantly higher by about 11%. Although there was no significant difference in trunk height, the palm in the compacted plots exhibited a significant reduction in trunk diameter by 9%, trunk dry weight by 8% and frond dry weight by 6% as compared to the control. Total leaf area was not affected as reflected in the optimum leaf area index (LAI) value. A greater root biomass was observed in the control,while the treated plots showed a decreasing trend in root biomass with increasing trailer weight. The reduction in total root biomass in the compacted plots was compensated by higher tertiary and quaternary roots biomass. This resulted in a significant increase in root surface area for better water and nutrient uptake as ompared to the control. The results indicated that six years of compaction treatments had affected the soil physical properties of this Bernam series soil, but it was nonlimiting to palm growth, since a positive relationship was found between these treatments and oil palm yield.